2000
DOI: 10.1148/radiology.217.3.r00dc30713
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Arterial Embolization: Factors Influencing Patient Radiation Exposure

Abstract: With operator experience and careful technique, uterine arterial embolization can be performed at radiation exposures comparable to those used in routine diagnostic studies. However, operators must be familiar with the technical parameters of their angiographic equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 15 publications
3
36
0
Order By: Relevance
“…Effective measures include optimized source-object, source-image, and object-image distances, the avoidance of magnification and oblique projections, tight collimation to the relevant anatomy, the use of pulsed fluoroscopy with decreased image frequency, and the use of low frame rates or even last-image-hold to document angiographic endpoints [9,13]. Flat panel detectors improve image quality while reducing radiation exposure, and pre-interventional optimization of the tube angle by 3D-reconstructed contrast-enhanced MR angiography helps to avoid conventional survey aortography [11,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective measures include optimized source-object, source-image, and object-image distances, the avoidance of magnification and oblique projections, tight collimation to the relevant anatomy, the use of pulsed fluoroscopy with decreased image frequency, and the use of low frame rates or even last-image-hold to document angiographic endpoints [9,13]. Flat panel detectors improve image quality while reducing radiation exposure, and pre-interventional optimization of the tube angle by 3D-reconstructed contrast-enhanced MR angiography helps to avoid conventional survey aortography [11,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Flat panel detectors improve image quality while reducing radiation exposure, and pre-interventional optimization of the tube angle by 3D-reconstructed contrast-enhanced MR angiography helps to avoid conventional survey aortography [11,22,23]. In particular, angiography units allowing the selection of lower pulse rates during fluoroscopy contribute to a significant reduction in the overall fluoroscopy time and the radiation dose exposure of patients undergoing UFE [9,24]. In the Artis Zeego Q angiography unit (Group 1), radiation dose has been further reduced by copper prefiltration and automatic exposure control.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation exposure occurring during UAE is a significant concern because many women who are candidates for the procedure are of childbearing age. With operator experience and limiting fluoroscopy time, the use of magnified and oblique views, non-pulsed fluoroscopy and road-mapping, the absorbed ovarian dose may be minimized (Andrews & Brown 2000;Binkert et al, 2001).…”
Section: Postprocedural Carementioning
confidence: 99%
“…Several methods have been suggested to reduce the dose, including bilateral femoral access and low imaging frame rates (10)(11)(12). Additionally, it has been shown that the interventionist's experience has a strong impact on reducing the number of runs needed to determine the best uterine artery (UA) catheterization angle, and therefore reducing the total radiation dose (13).…”
mentioning
confidence: 99%
“…This initially chosen projection is often suboptimal, and one or even several additional X-ray acquisitions are performed before the UA can be catheterized. DSA acquisitions are a major contributor to the total radiation administered to the patient (13). Therefore, minimizing the number of DSA runs has been associated with a lower patient dose and a reduction of the amount of administered iodinated contrast medium (14).…”
mentioning
confidence: 99%